In Vivo Efficacy and Toxicity of Curcumin Nanoparticles in Breast Cancer Treatment: A Systematic Review - Ombredane, Alicia S.; Silva, Vitória R. P.; Andrade, Laise R.; Pinheiro, Willie O.; Simonelly, Mayara; Oliveira, Jaqueline V.; Pinheiro, Andréia C.; Gonçalves, Gabriel F.; Felice, Gisela J.; Garcia, Mônica P.; Campos, Patrícia M.; Luz, Glécia V. S.; et al. (Frontiers in Oncology, 2021)
Breast cancer is one of the most prevalent types of malignant tumors in the world, resulting in a high incidence of death. The development of new molecules and technologies aiming to apply more effective and safer therapy strategies has been intensively explored to overcome this situation. The association of nanoparticles with known antitumor compounds (including plant-derived molecules such as curcumin) has been considered an effective approach to enhance tumor growth suppression and reduce adverse effects. Therefore, the objective of this systematic review was to summarize published data regarding evaluations about efficacy and toxicity of curcumin nanoparticles (Cur-NPs) in in vivo models of breast cancer. The search was carried out in the databases: Cinahl, Cochrane, LILACS, EMBASE, FSTA, MEDLINE, Proquest, BSV regional portal, PubMed, ScienceDirect, Scopus, and Web of Science. Studies that evaluated tumor growth in in vivo models of breast cancer and showed outcomes related to Cur-NP treatment (without association with other antitumor molecules) were included. Of the 528 initially gathered studies, 26 met the inclusion criteria. These studies showed that a wide variety of NP platforms have been used to deliver curcumin (e.g. micelles, polymeric, lipid-based, metallic). Attachment of poly(ethylene glycol) chains (PEG) and active targeting moieties were also evaluated. Cur-NPs significantly reduced tumor volume/ weight, inhibited cancer cell proliferation, and increased tumor apoptosis and necrosis. Decreases in cancer stem cell population and angiogenesis were also reported. All the studies that evaluated toxicity considered Cur-NP treatment to be safe regarding hematological/biochemical markers, damage to major organs, and/or weight loss. These effects were observed in different in vivo models of breast cancer (e.g. estrogen receptor-positive, triple-negative, chemically induced) showing better outcomes when compared to treatments with free curcumin or negative controls. This systematic review supports the proposal that Cur-NP is an effective and safe therapeutic approach in in vivo models of breast cancer, reinforcing the currently available evidence that it should be further analyzed in clinical trials for breast cancer treatments.